Improving Fun Learning in Science Subjects by Using Monopoly Game Media - Abdul Latief; Niki Novalia (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To find out the increase in fun learning in science subjects using monopoly game media in class IV SD Negeri 13/1 Muara Bulian. Methodology: This research method is classroom action research. In this study there were three cycles, in one cycle carrying out two meetings. There are four procedures of this study, namely planning, implementation, observation and reflection. Main Findings: The results of this study are that the use of monopoly games can increase fun learning in Science class IV SD Negeri 13/1 Muara Bulian. The monopoly game used in science learning is different from the monopoly game in general, namely giving quizzes in the form of questions from the material students have studied. It makes students relax, students' attention is devoted, enthusiastic, happy, high concentration and safe when learning takes place. Novelty/Originality of this study: Increase knowledge about the use of monopoly game media as a learning medium to increase fun learning.